Improving Learning Outcomes of PAI and Ethics Using Learning Video Media In Class VIII SLB Al-Azra’iyah - Hilma Akmalia (BiCED Proceeding, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education and Character Education in the 8th grade at SLB Al-Azra'iyah through the use of educational video media. The research employed Classroom Action Research (CAR) with both qualitative and quantitative approaches. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The results showed that the use of educational video media enhanced student engagement, understanding of the material, and learning outcomes. Although there was improvement, the classical mastery of students in Cycle I did not meet the expected criteria, with only 33.33% of students reaching the Minimum Completeness Criteria (KKM). In Cycle II, with improved strategies, significant progress was noted, demonstrating that educational video media can be an effective tool for enhancing student motivation and learning outcomes. Based on these findings, it is recommended that the use of video media be accompanied by interactive approaches and further support for students who face difficulties.